FENOMENA NGELAGA PADA MASYARAKAT DESA ADAT PESABAN, KECAMATAN RENDANG, KABUPATEN KARANGASEM - Juliarsana, I Gede Ari; Kamajaya, Gede; Krisna Aditya, I Gusti Ngurah Agung; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
Bali is one area that is famous for its rich traditions. One of the traditions in Balinese society is the ngayah tradition. However, as time went on, the ngayah tradition began to experience a shift due to changes in livelihoods from the agricultural sector to industry, especially the tourism industry. Through this change, many rural communities in Bali have migrated to industrial and tourism centers, namely Denpasar and Badung, which of course results in them being tied to working hours. The people who migrate then face the problem of dividing their time between jobs and their obligation to do piodalan work in the village. One of the villages facing this problem is the Pesaban Traditional Village, which then implemented the meli Ayahan policy, which is known as ngelaga. However, in the course of its journey, the emergence of this ngelaga phenomenon ultimately led to pros and cons in the midst of Pesaban customary village residents. This research uses a qualitative descriptive explanative approach. William F. Ogburn's cultural lag theory is used as a scalpel to analyze the pros and cons of applying ngelaga in the Pesaban Traditional Village. The form of pro krama is obedience to paying dues and spending time doing physical activities in spare time, while the form of the contra is the existence of pakrimik and medaya. The emergence of these pros and cons due to the gap in acceptance of cultural diffusion between the younger generation and the older generation. It was concluded that fighting is a solution for wandering krama who face time problems. It is suggested that the government seek the right formulation to deal with this problem in the future.   Keyword : Ngelaga , Desa Adat Pesaban, Piodalan , Krama , Cultural Lag